Early Detection of Ratoon Stunting Diseases in Sugarcane Seeds Using Polymerase Chain Reaction Method - Wijayanti Kristiana Sri; Hidayah Nurul; Yulianti Titiek; Supriyono; Nurindah; Sunarto Dwi Adi; Sujak; Subiyakto; Indrayani Igaa; Utari Dewi (BIO Web of Conferences, 2024)
Sugarcane is a kind of plantation crop that can be used as a raw material for the sugar industry. The productivity of sugarcane can be influenced by several factors, including infection of pathogenic bacteria such as Leifsonia xyli f.sp. xyli (Lxx), the causal agent of Ratoon Stunting Disease (RSD) in sugarcane. The disease is one of the major diseases of sugarcane worldwide. RSD is symptomless unless the disease incidence is severe. The Polymerase Chain Reaction (PCR) method is generally known for detecting plant pathogens. However, there is still limited information on the detection of RSD using PCR. Therefore, our study aimed to detect the existence of RSD in sugarcane seeds using the PCR method. Three sugarcane varieties were used in this study, including AAS Agribun, AMS Agribun, and BQ (positive control of RSD). We did sample the stems and midribs of those three varieties at the age of 3 and 7 months. The results showed that Lxx was found both in the stem and midrib of sugarcane variety BQ at the age of 3 and 7 months. These results indicated that the PCR method can be used for early detection of RSD in sugarcane seeds.